Pemisahan Harta Bersama Melalui Perjanjian Perkawinan yang Dibuat oleh Pasangan Perkawinan Campuran Setelah Perkawinan Dilangsungkan Dikaitkan dengan Undang-Undang Perkawinan dan Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 - Farras Nafisa; Susilowati Suparto (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The purpose of this research is to determine the position of existing common property before the creation of a marriage agreement by mixed-marriage couples after the marriage has taken place. Additionally, it aims to understand the legal consequences of marriage agreements made by mixed-marriage couples after the marriage, particularly regarding the ownership of common property, in accordance with Law Number 1 of 1974 concerning Marriage post-Constitutional Court Decision Number 69/PUU-XIII/2015. This research employs a normative juridical method with a descriptive-analytical research specification, connecting issues comprehensively based on relevant legal regulations. Data collection techniques include literature review and field study conducted through interviews at the Notary and PPAT Office. The research results indicate that the position of common property that existed before the creation of the marriage agreement by mixed-marriage couples after the marriage remains as joint property. However, the separation of common property can be applied after the marriage agreement is made. The legal consequences regarding common property depend on the type of asset. If the common property includes immovable assets such as land in Indonesia, it becomes the property of the Indonesian citizen. As for movable common property, it is adjusted based on the agreement between the parties. The legal consequences of marriage agreements made after marriage concerning common property that is already involved with third parties will be binding on the third party. It is advisable to keep it as common property to avoid harming third parties.